2020
DOI: 10.1016/j.immuni.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Epitopes Are Recognized by a Public and Diverse Repertoire of Human T Cell Receptors

Abstract: Understanding the hallmarks of the immune response to SARS-CoV-2 is critical for fighting the COVID-19 pandemic. We assessed antibody and T cell reactivity in convalescent COVID-19 patients and healthy donors sampled both prior to and during the pandemic. Healthy donors examined during the pandemic exhibited increased numbers of SARS-CoV-2-specific T cells, but no humoral response. Their probable exposure to the virus resulted in either asymptomatic infection without antibody secretion, or activation of pre-ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
296
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(341 citation statements)
references
References 73 publications
37
296
1
7
Order By: Relevance
“…( Schultheiß et al., 2020 ), Shomuradova et al. ( Shomuradova et al., 2020 ) and Alsoussi et al. ( Alsoussi et al., 2020 ).…”
Section: Methodsunclassified
“…( Schultheiß et al., 2020 ), Shomuradova et al. ( Shomuradova et al., 2020 ) and Alsoussi et al. ( Alsoussi et al., 2020 ).…”
Section: Methodsunclassified
“…This data has started to emerge from immunological assays that analyze immune responses in COVID-19 patients. As of 8 September 2020, we found eight experimental studies [ 8 , 9 , 115 , [176] , [177] , [178] , [179] , [180] ], reviewed in [ 181 ], as well as an additional study [ 182 ], that reported positive T cell immune responses from blood samples of convalescent COVID-19 patients against epitopes derived from SARS-CoV-2 proteins. Compiling data from these nine studies yielded a total of 324 (unique) epitopes.…”
Section: Correspondence Between Predicted and Experimentally-determinmentioning
confidence: 99%
“…Of these, some studies obtained a set of peptides to synthesize using one or more of the in silico epitope prediction methods, which were then used to stimulate the PBMCs. Three such studies [ 8 , 9 , 180 ] used NetMHCpan-4.0, two studies [ 177 , 182 ] used NetMHC4.0, while one study [ 115 ] used HLAThena and NeonMHC2 to select the set of peptides to synthesize. Two of these studies [ 8 , 182 ] also investigated a few epitopes that were predicted in [ 20 , 22 ] using SARS-CoV immunological data.…”
Section: Correspondence Between Predicted and Experimentally-determinmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunodominant SARS-CoV-2 antigen specificities have been identified with unprecedented speed for an emerging pathogen, and phenotypic characterization of antigen-reactive T cells has quickly been performed by a plethora of studies 6,7,16,[8][9][10][11][12][13][14][15] . While there is general agreement that SARS-CoV-2-reactive T cells are activated and differentiate during the course of the immune response, the extents of activation and differentiation are controversial 4,5 .…”
Section: Main Textmentioning
confidence: 99%